2013
DOI: 10.4319/lo.2013.58.4.1501
|View full text |Cite
|
Sign up to set email alerts
|

Colimitation of the unicellular photosynthetic diazotroph Crocosphaera watsonii by phosphorus, light, and carbon dioxide

Abstract: We describe interactive effects of total phosphorus (total P 5 0.1-4.0 mmol L 21 ; added as H 2 NaPO 4 ), irradiance (40 and 150 mmol quanta m 22 s 21 ), and the partial pressure of carbon dioxide (P CO2 ; 19 and 81 Pa, i.e., 190 and 800 ppm) on growth and CO 2 -and dinitrogen (N 2 )-fixation rates of the unicellular N 2 -fixing cyanobacterium Crocosphaera watsonii (WH0003) isolated from the Pacific Ocean near Hawaii. In semicontinuous cultures of C. watsonii, elevated P CO2 positively affected growth and CO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 43 publications
(79 reference statements)
1
34
0
Order By: Relevance
“…N 2 fixation rates were significantly reduced in the ocean acidification treatment compared to the ambient scenario in the light. Other studies reported an increase of N 2 fixation activity under elevated CO 2 conditions for planktonic cyanobacteria due to increased photosynthetic carbon fixation by overcoming CO 2 limitation (Hutchins et al 2007, Garcia et al 2013. This may be the case for planktonic autotrophic diazotrophs, but CO 2 limitation is unlikely to occur in the S. hystrix holobiont due to respiration by the coral host.…”
Section: Discussionmentioning
confidence: 95%
“…N 2 fixation rates were significantly reduced in the ocean acidification treatment compared to the ambient scenario in the light. Other studies reported an increase of N 2 fixation activity under elevated CO 2 conditions for planktonic cyanobacteria due to increased photosynthetic carbon fixation by overcoming CO 2 limitation (Hutchins et al 2007, Garcia et al 2013. This may be the case for planktonic autotrophic diazotrophs, but CO 2 limitation is unlikely to occur in the S. hystrix holobiont due to respiration by the coral host.…”
Section: Discussionmentioning
confidence: 95%
“…Cultures were acclimated to low-P conditions as described by Garcia et al (2013). Briefly, after establishment of steady-state growth at each P concentration, cultures were then successively transferred to the neighboring lower P treatment until a new steady-state growth rate was achieved before sampling and further transfers.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, these measurements in the lowest P treatments in experiments with Trichodesmium and Crocosphaera were considered to represent values where the growth rate approached zero. We calculated growth rates as described previously (Garcia et al, 2013) using volumespecific estimates of cell number or total filament length. Hyperbolic functions of the form f (x) ¼ ax/(b þ x) were fit to the data in Figure 1 using an iterative method (Garcia et al, 2013) with Sigma Plot 10 software, where a ¼ m max , b ¼ Km and C min is the minimum concentration of P needed to support growth.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations